Politics and higher education in East Africa from the 1920s to 1970 - Mngomezulu, Bhekithemba Richard (UJ Press, 2022)
The main objective of this book is to establish the salient reasons why higher education was developed in East Africa and specifically why the Federal University of East Africa was constituted. The book will identify the factors responsible for the collapse of this regional institution in June 1970. Another objective of this book is to demonstrate how the history of the University of East Africa sheds light on colonial and post-colonial policies on education, especially higher education, as a contribution to educational planning in contemporary Africa.